PENGOLAHAN LIMBAH MINYAK GORENG MENJADI SABUN CUCI EKONOMIS BERBASIS EKONOMI SIRKULAR DI DESA TANJUNG PUTUS KEC. PADANG TUALANG KABUPATEN LANGKAT - Sri Ahadah Nuril Fajar; Cahaya Permata; Rahita Rahmadya Waluyo; Arya Andika; Maya Utami (Yayasan Haiah Nusratul Islam, Indonesia, 2025)
One of the programs of the Community Service Program (KKN) in Tanjung Putus Village focuses on processing used cooking oil as a form of circular economy. This activity aims to reduce environmental pollution while increasing the economic value of the community through training in making environmentally friendly soap. The research method used is PAR (Participatory Action Research) with several stages, namely 1. problem identification stage (planning), 2. action planning stage, 3. implementation stage (action), 4. observation stage. The results of the activity show that the soap produced has a solid physical quality, good washing power, and a pH range of 8–9, which is safe for everyday use. The enthusiasm of the community, especially housewives, was evident from their active participation in the training and the formation of small groups to manage used cooking oil. The tangible impacts of this program include reduced environmental pollution, improved skills, and new business opportunities for local villagers. Thus, processing used cooking oil into soap not only solves the problem of household waste but also serves as a model for sustainable community empowerment based on a circular economy.